ELECTRONIC MARKETING ARCHITECTURE FOR BANANA FLAVOR SNACK UMKM USING THE ENTERPRISE ARCHITECTURE PLANNING MODEL - Arida, Syiar Irmania; Nurheti, Nurheti; Salim, Agus (STMIK Pringsewu, 2023)
In an increasingly developing digital era, electronic marketing (e-marketing) has become key for Micro, Small, and Medium Enterprises (MSMEs) in increasing Power competitiveness and market reach. Study This aims to develop electronic marketing architecture for mobile MSMEs in banana flavored snack industry uses the approach of Enterprise Architecture Planning (EAP). Using EAP, research This try compile a framework of systematic and comprehensive work for planning, designing, and implementing marketing strategies for effective electronics. Application method Enterprise Architecture Planning (EAP) specifically for deep flavor banana snack industry MSME context. Approach This covers an analysis of technology and business processes and considers aspects of typical of local culture and markets from industry the. Additionally, the research will develop an integrating architectural model for various component technology information, such as e-commerce platforms, social media, and data analytics, to support adaptive and responsive marketing strategies. Result of study This expected can give a guide practical for MSMEs, deep-flavored banana snacks optimizing utilization digital technology for increase performance business they.